Growth and computational studies on vanillin isoniazid single crystals - Mugeshini, S. (Elsevier, 2021)
In this paper, we performed the synthesis, characterization, and computational studies on Vanillin isoniazid (VIN) single crystals grown by the slow evaporation solution growth technique. The crystalline perfection and monoclinic crystal structure with space group Cc have been confirmed using single-crystal X-ray diffraction and powder X-ray diffraction method. The presence of various functional groups has been identified by FTIR and Raman spectroscopy. These data are in good agreement with theoretical and experimental values of FT-IR, FT-Raman.The optical absorption studies were carried out for the grown crystal VIN which has been analyzed by UV-Vis-NIR spectroscopy. Thermogravimetric (TG) and differential thermal analysis (DTA) were carried out to characterize the thermal stability of the VIN crystals. The quantum chemical calculations for VIN crystal are performed at the B3LYP, B3PW91, levels of theory with the 6-311++G(d,p) basis set. Finally, inter-and intramolecular charge transfer, hyper conjugative interaction of the compound is investigated from natural bond orbital (NBO) analysis. The Mulliken atomic charge of VIN single crystal has been investigated using theoretical calculations.